Who gains from credit granted between firms? Evidence from inter-corporate loan announcements made in China - Qing He; Liping Lu; Steven Ongena (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
​Who gains from inter-corporate credit? To answer this question we investigate the reactions of the stock prices of both the issuing and receiving firms to the announcements of 719 inter-corporate loans that took place between 2005 and 2012 in China. We find that the average abnormal return for the issuers of inter-corporate loans is significantly negative, whereas the corresponding return for those firms receiving credit is positive. Investors may worry that issuing firms may have run out of other worthwhile projects to finance, while at the same time they may view credit-receiving firms as being certified as worthy borrowers. The issuance of intra-group loans, especially those with higher interest rates, is associated with lower returns overall since such loans may signal a spreading of financial distress to the rest of the group. After issuing inter-corporate loans, firms are also found to have lower accounting performance, which confirms the aforementioned signaling interpretation.
URN:NBN:fi:bof-201501261018
Keywords: G30; G14; G21; 330